Perlindungan Hukum Terhadap Pekerja Anak Yang Berkerja Pada Grup Calempong di Kecamatan Kampa Kabupaten Kampar Ditinjau Dari Undang-undang Nomor 13 Tahun 2003 - Wilis, Erna; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal protection for child laborers working in the calempong group in the sub-district of Kampadistrict needs to be implemented, because there are still many employers who consider that workers areworkers who can be as they please. The consequences are that many workers as human beings and asviolated children, workers in child labor must be personal and must comply with applicable rules.The problems that were carried out were the first thing that was done at the Calempong Group inKampa Subdistrict with Law Number 13 of 2003 concerning Manpower and Second Efforts made to providelegal protection for child labor. The research method used is research, the other is legal research which isalso called research and this research is descriptive. Data in the data, the type of data used in this study areprimary and secondary data, namely directly through respondents (field), Law No. 13 of 2003 concerningEmployment, Civil Code, Kampar Regional Regulation No. 10 of 2016 , legal journals and books thatdiscuss research. Analysis of this data is done qualitatively and deductively drawn conclusions.Based on the results of the research conducted by the author, it was found that there were rights ofchild workers violated by Calempong businessmen, and child laborers were not directly disadvantaged, atthis time needed protection for children working in the calempong group in the sub-district kampa kampardistrictKeywords: Child labor - Legal protection - Child labor rights.